THE ROLE OF ACCOUNTING KNOWLEDGE IN ENHANCING CONFIDENCE IN COMPANIES’ ACCOUNTING DISCLOSURES IN THE ALGERIAN ACCOUNTING ENVIRONMENT - SAIDAT, Mokhtar; KHEMGANI , Badrazzaman (The journal of contemporary issues in business and government, 2024)
This study aims to highlight the role of accounting knowledge in enhancing confidence in companies’ accounting disclosures in the Algerian accounting environment through the challenges faced by accountants in Algeria. To address the study problem and test the hypotheses, a descriptive analysis method and the SPSS program were used to analyze the correlation between the accounting knowledge and the confidence in accounting disclosures for companies in the Algerian accounting environment. The study concluded that accounting knowledge contributes significantly to enhancing confidence in companies’ accounting disclosures.